Sustainable Forest Management Practices to Combat Deforestation (West African Journal on Sustainable Development, 2024)
Deforestation has a devastating impact on the environment and society. When forests are cleared for agriculture, logging or development, it leads to a loss of habitat for wildlife and disrupts the ecosystem. Forests are essential in regulating the Earth's climate by absorbing large amounts of carbon dioxide and releasing oxygen. Sustainable forest management (SFM) is the management of forests according to the principles of sustainable development. Sustainable forest management must keep a balance between the three main pillars: ecological, economic and socio-cultural. The goal of sustainable forestry is to allow for a balance to be found between making use of trees while maintaining natural patterns of disturbance and regeneration. We review several techniques for managing a forest sustainably. These strategies include: Adopting sustainable forestry practices that prioritise the long-term health and productivity of forest ecosystems. This includes selectively harvesting trees, replanting and restoring degraded areas, and ensuring sufficient wildlife habitat is preserved. Reducing or eliminating clearcut logging, a method that involves removing entire forests in one go, leads to significant ecosystem disruption. Alternative approaches include selective logging, where only mature trees are harvested, or shelterwood logging, where younger trees remain in place to provide habitat for wildlife and promote forest regeneration. Protecting primary and intact forests, as these ecosystems have remained largely undisturbed by human activities. These areas are essential for maintaining biodiversity and storing carbon, making them vital to the fight against climate change and biodiversity loss. Implementing stricter deforestation regulations, including setting limits on how much forest can be harvested, the methods used, and ensuring that companies compensate for any damage caused. Governments can also provide incentives to companies that prioritise sustainable forestry practices and levy fines and penalties for breaches of deforestation regulations. Encouraging the use of recycled and alternative materials can also reduce the demand for newly harvested timber and promote responsible forestry management. This includes using recycled paper products, alternative building materials such as bamboo or recycled plastic, and supporting the development of sustainable production methods.
Keywords: Sustainable; Forest; Management; Deforestation